2018
DOI: 10.1177/1087054718808599
|View full text |Cite
|
Sign up to set email alerts
|

The Underestimated Role of Refractive Error (Hyperopia, Myopia, and Astigmatism) and Strabismus in Children With ADHD

Abstract: Objective: To examine the association of refractive error (myopia, hyperopia, astigmatism) and strabismus with ADHD. Method: Based on data from the large, representative, epidemiological sample of the German Health Interview and Examination Survey for Children and Adolescents (KiGGS) study (N = 13,488), the associations of myopia, hyperopia, astigmatism, and strabismus with ADHD were examined, with and without consideration of other common ADHD risk factors. Results: In single logistic regression models, all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…Common vision anomalies that remain untreated have been reported to affect reading and academic performance, in particular uncorrected hyperopia (Kulp et al, 2016;Narayanasamy et al, 2015a;Rosner & Rosner, 1997;Shankar et al, 2007;van Rijn et al, 2014), uncorrected astigmatism (Harvey et al, 2016;Narayanasamy et al, 2015b), and reduced stereoacuity (Kulp et al, 2016). Furthermore, vision anomalies have been reported to be more prevalent in children and adolescents with dyslexia compared with controls (Vikesdal et al, 2020), and hyperopia, astigmatism, and strabismus are reported to be associated with attention deficit hyperactivity disorder (Reimelt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Common vision anomalies that remain untreated have been reported to affect reading and academic performance, in particular uncorrected hyperopia (Kulp et al, 2016;Narayanasamy et al, 2015a;Rosner & Rosner, 1997;Shankar et al, 2007;van Rijn et al, 2014), uncorrected astigmatism (Harvey et al, 2016;Narayanasamy et al, 2015b), and reduced stereoacuity (Kulp et al, 2016). Furthermore, vision anomalies have been reported to be more prevalent in children and adolescents with dyslexia compared with controls (Vikesdal et al, 2020), and hyperopia, astigmatism, and strabismus are reported to be associated with attention deficit hyperactivity disorder (Reimelt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Garnet et al found a threefold increase in the incidence of ADHD among patients with convergence insufficiency compared with the general population in a retrospective study [26]. In a large-scale cohort study by Reimelt et al, strabismus and refractive error were linked to ADHD [28]. In another large-scale cross-sectional telephone survey in the United States [29], children with eye problems had a higher prevalence of ADHD (15.6%) than those with normal vision (8.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal visual experience may cause asthenopia and inattentiveness. Researches [32,33] considered that refractive error seemed to be leaded to symptoms of inattention and hyperactive activity independently. Our study found that corrected visual acuity of the left eye was negatively correlated with SNAP positive result.…”
Section: Discussionmentioning
confidence: 99%